Impact of the inflammation on the outcomes of catheter ablation of drug‐refractory ventricular tachycardia in cardiac sarcoidosis. (27th January 2020) - Kaur, Daljeet; Roukoz, Henri; Shah, Mandar; Yalagudri, Sachin; Pandurangi, Ulhas; Chennapragada, Sridevi; Narasimhan, Calambur
Abstract: Introduction: Catheter ablation (CA) of ventricular tachycardia (VT) in cardiac sarcoidosis (CS) has been reported with varying success. However, there is a scarcity of data on the outcomes of CA based on ongoing inflammation. Objective: We hypothesized that the response to VT ablation depends upon the stage of the disease. Methods: Between July 2004 and December 2018, 24 patients of CS presented with drug‐refractory VT at CARE Hospital (Hyderabad) and the University of Minnesota (Minneapolis, MN). Patients were classified into two groups based on cardiac magnetic resonance imaging and positron emission tomography: (a) inflammatory phase, (b) scar phase. All patients underwent 3D electro‐anatomic mapping guided CA. Results: The clinical VT was ablated in all but one patient. In 16 patients (66.6%), both the clinical and nonclinical VTs were ablated (complete success), while in seven patients (29.1%) nonclinical VTs was still inducible. In patients with inflammation (group A), complete success for VT ablation was achieved in 10 out of 17 (58.8%). In patients without inflammation (group B), complete success was achieved in six out of seven patients (85.7%). Eleven patients (45.8%) had a recurrence of VT. Among patients in the inflammatory phase (group A): 10 out of 17 patients had a recurrence of VT, while only one out of seven patients in the scar phase (group B) had VT recurrence over a mean follow‐up of 5.7 ± 3.9 years. Epicardial ablation was performed in 10 (41.6%) patients. Conclusion: CA of drug‐refractory VT in CS is effective, often requiring the epicardial approach. Incomplete success and recurrence of VT were higher in the inflammatory phase of the disease.